Sílabas métricas em Terenciano Mauro, De Syllabis, 997-1299 - Pizano, Mariana Peixoto [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This monograph addresses to the study of Latin metrical notions and concepts as showed in the volume VI of Heinrich Keil’s work, entitled Grammatici Latini (GL): Scriptores Artis Metricae. From that book, it was chosen Terentianus Maurus’s work for corpus, particularly the excerpt between verses 997 and 1299 of De Syllabis, a part of Terentianus’s De Litteris, De Syllabis, De Metris, which is a metric manual written in verses. Until now, there are only three translations of that text into modern languages: two in Italian (one of them was used for comparison with the translation prepared for this monograph) and a French one. That work still contains many reference notes whenever Terentianus Maurus uses ancient authors to demonstrate his explanations on Metrics. Thus this research intends to join in other analysis made on Latin metrical manuals that have already been translated or are still going to be, as well as to notice the importance and the specific value of meter in ancient poetry

Este trabalho dedica-se ao estudo de noções e conceitos referentes à métrica latina contidos no volume VI da obra de Heinrich Keil, intitulado Grammatici Latini (GL): Scriptores Artis Metricae. O autor escolhido foi Terenciano Mauro e o córpus analisado compreende o intervalo de versos 997 a 1299 do De Syllabis, contido em Terentianus De Litteris, De Syllabis, De metris. A obra consiste em um manual de métrica escrito em versos. Até o presente momento existem somente três traduções deste material em línguas modernas: duas em italiano (uma delas utilizada para cotejo das traduções realizadas nesta pesquisa) e uma versão francesa. O trabalho também conta com diversas notas de referência sempre que Terenciano Mauro faz uso de passagens de outros autores antigos para demonstrar suas explicações. O material escolhido para análise pretende juntar-se a outros manuais de métrica latina que já tenham tradução ou ainda venham a ser traduzidos e analisados, bem como levar a perceber a importância e o peso específico do metro na poesia antiga
Keywords: Mauro, Terenciano, De Syllabis - Crítica e interpretação; Poesia classica; Literatura latina; Gramatica